Use of ADAM‐C and CHA2DS2‐VASc scores to predict complex aortic atheroma after brain ischemia: A prospective observational study. Issue 4 (25th March 2021) - Nicot, Florence; Charbonnel, Clément; Jego, Christophe; Jourda, François; Vinsonneau, Ulric; Garçon, Philippe; Turlotte, Guillaume; Rivière, Jean François; Maurin, Marion; Lubret, Rémy; Meimoun, Patrick; Akret, Chrystelle; et al.
Abstract: Background and aims: Complex aortic atheroma (CAA) is a common cause of acute brain ischemia (BI), including ischemic stroke (IS) and transient ischemic attack (TIA), and is associated with recurrence. The CHA2DS2‐VASc score is a useful tool for predicting stroke in patients with atrial fibrillation (AF), and can also predict cardiovascular events in other populations, including non‐AF populations. The ADAM‐C score is a new risk score for predicting the diagnostic yield of transesophageal echocardiography (TEE) after BI. We aimed to evaluate the ability of CHA2DS2‐VASc and ADAM‐C scores to predict CAA after BI. Methods: This prospective, multicenter, observational study included 1479 patients aged over 18 years who were hospitalized for BI. CAA was defined as the presence of one or more of the following criteria: thrombus, ulcerated plaque, or plaque thickening ≥ 4 mm. Results: CAA was diagnosed in 216 patients (14.6%). CHA2DS2‐VASc and ADAM‐C scores were significantly higher in the CAA group versus the non‐CAA group ( P  < .0001 for both). The CHA2DS2‐VASc and ADAM‐C scores appear to be good predictors of CAA (AUC 0.699 [0.635, 0.761] and 0.759 [0.702, 0.814], respectively). The sensitivity, specificity, predictive positive value (PPV), and negative predictive value (NPV) of the scores for detecting CAA were 94%, 22%, 17%, and 96%, respectively, for a CHA2DS2‐VASc score < 2, and 90%, 46%, 22%, and 96%, respectively, for an ADAM‐C score < 3 Conclusions: CHA2DS2‐VASc and ADAM‐C scores are able to predict CAA after BI. CHA2DS2‐VASc < 2 and ADAM‐C < 3 both have an interesting NPV of 96%.